Comparative analysis of stress levels and quality of life among medical students in Southern Asia and South Caucasus - Kurup, R. Gowri; Kumar, Janardanan (International Journal Of Community Medicine And Public Health, 2024)
Background: Medicine is a challenging study and is known for its demanding nature. This also results in increased stress levels among students. Understanding factors that influence stress and quality of life from medical students in different regions is important for the development of effective interventions and support systems. Methods: A meticulous quantitative method approach has been utilized. This research is done via data fetched through a questionnaire. Statistical analyses are comprised of t-tests and correlation tests to employ a dissection of quantitative data while the data is subjected to analysis to uncover the underlying patterns and nuances. These results showcase crucial disparities in the stress levels between medical students in Southern Asia and the South Caucasus while imparting light on factors impacting the quality of life experienced by students in both regions. Results: The implications of this study hold primary significance for sharing information with targeted interventions with an aim at bolstering the mental health and academic performance of medical students in both the areas of Southern Asia and the South Caucasus. Conclusions: The major objective of this study is to hold comparisons of stress levels and quality aspects of life in Southern Asia and South Caucasus, with the identification of the multifaceted factors that contribute to the stress levels among students in both regions, understanding the various challenges and sharing a glimpse of actionable implications for interventions which are aimed at bolstering students’ well-being.